Prevalence and Associated Risk Factors of Eimeria bovis and Eimeria zuernii in Kacha Bira District, Central Ethiopia - Mesfin Mathewos; Habtamu Endale (Veterinary Medicine International)
Background. Eimeriosis, which is caused by several Eimeria species, is a protozoan disease affecting the cattle worldwide. The current investigation was aimed at ascertaining the prevalence of bovine eimeriosis, evaluation of the involved risk variables, and identification of the several Eimeria species that were prevalent in the Kacha Bira district of central Ethiopia. Methods. A cross-sectional coprological assessment of Bovine coccidiosis and its associated risk factors through a simple random sampling technique was conducted from January 2021 to December 2022. Results. The cumulative prevalence of coccidia was 17.83% (82/460) in the current investigation, with Eimeria bovis, Eimeria zuernii, and mixed infections having a respective prevalence of 7.83%, 3.25%, and 6.74%. From the anticipated risk factors, cattle age and months of the year have revealed a statistically significant (p<0.05) association with the prevalence of eimeriosis in the cattle under investigation. However, there were no statistically significant (p>0.05) relationships between the coccidia infection and the sex and breed of cattle and the season. Conclusion. During the study, a high prevalence rate of bovine eimeriosis was recorded. Thus, a further detailed study involving molecular techniques to identify prevailing Eimeria species is paramount to develop and put into effect evidence-based control strategies to tackle the prevalence and subsequent effect of eimeriosis.